Coexistence, Extinction and Survival—The Evolutionary History of Bison Species in Western Eurasia - Bastien Llamas; Ayla L. van Loenen; Kieren J. Mitchell; Emilia Hofman‐Kamińska; Hervé Bocherens; Holly Heiniger; Martina Pacher; Daniel Makowiecki; Giedrė Piličiauskienė; Dorothée G. Drucker; David Brown; Zoe A. Thomas; et al. (Global Change Biology, 2025)
European bison ( Bison bonasus ) are one of the few European megafaunal species to survive the Late Pleistocene mass megafaunal extinction. Current conservation management efforts have proceeded in the absence of information about their evolutionary history, which has been obscured by recent severe population bottlenecks. We characterized mitochondrial genomes from 135 ancient bison samples spanning > 50,000 years (> 50 ka) across the Eurasian continent and detected three distinct phylogenetic groups: two distinct clades of European bison and the extinct steppe bison ( Bison priscus ). The geographical distributions and dietary/ecological signatures of the three groups overlapped during the Late Pleistocene climate cycles and tracked environmental changes including vegetation cover and human impacts. The abundance of European bison specimens responded negatively to the extent of forest cover, including Holocene cycles of abrupt atmospheric‐ocean circulation changes originating in the North Atlantic. European bison remain preferentially adapted to an open environment, but with today's anthropogenic landscapes, are now largely restricted to forest habitats with negative implications under scenarios of future environmental change.